A new class of electrolytes based on magnesium bis(diisopropyl)amide for magnesium–sulfur batteries. Issue 43 (8th May 2019) - Zhao, Xinghe; Yang, Yuanying; NuLi, Yanna; Li, Dongyu; Wang, Yurui; Xiang, Xuelin
Abstract : A new class of electrolytes for Mg–S batteries prepared by a facile in situ reaction of magnesium bis(diisopropyl)amide (MBA) with AlCl3, which show reasonable ionic conductivity and relatively high anodic stability on stainless steel, close to 100% Mg deposition–dissolution efficiency and high cycling reversibility and compatibility with the S cathode. Abstract : We present a new class of electrolytes, which has relatively high anodic stability on stainless steel (2.65 V, vs. Mg RE), low over-potential for Mg plating/stripping and close to 100% coulombic efficiency, for Mg–S batteries prepared by a facile in situ reaction of commercial magnesium bis(diisopropyl)amide (MBA) with AlCl3, The resulting Mg–S battery shows a highly stable discharge capacity of approximately 540 mA h g −1 for 30 cycles and one well-defined voltage plateau of about 1.1 V vs. Mg.